2016
DOI: 10.1002/adma.201505127
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Nanobrushes Made using Ambient Droplet Sprays

Abstract: An ambient solution-state method for making uniform nanobrushes composed of oriented 1D silver nanowires (NWs) with aspect ratios of 10(2) -10(4) is reported. These structures are grown over cm(2) areas on conducting surfaces. Assemblies of NWs form uniform nanobrush structures, which can capture micrometer-sized objects, such as bacteria and particulate matter. Variation in composition produces unique structures with catalytic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
(11 reference statements)
0
38
0
Order By: Relevance
“…While synthesis of new molecules in sprays was observed before, bulk synthesis of molecules with which characterization is possible was not attempted earlier. Using a home-built nano-electrospray source, Sarkar et al 127 showed that spraying an aqueous solution of silver acetate (AgOAc) over a TEM grid, resulted in the formation of 1D nanowire structures of Ag NPs (Fig. 18).…”
Section: Mass Spectrometry As a Tool For Materials Synthesismentioning
confidence: 99%
“…While synthesis of new molecules in sprays was observed before, bulk synthesis of molecules with which characterization is possible was not attempted earlier. Using a home-built nano-electrospray source, Sarkar et al 127 showed that spraying an aqueous solution of silver acetate (AgOAc) over a TEM grid, resulted in the formation of 1D nanowire structures of Ag NPs (Fig. 18).…”
Section: Mass Spectrometry As a Tool For Materials Synthesismentioning
confidence: 99%
“…Moreover, Cooks prepared metallic nanobrushes by exploitation of the Coulombic forces present in the electrolytic spray system; this is expected to generate interest in this method for creating metallic crystals, thanks to its ease in fabricating such structures directly from solutions and the efficient control of size and composition. [24] Therefore, ES technology has the potential to grow to become one of the future mainstream technologies for controlled preparation of crystals. Sodium chloride, one of the simplest crystal systems, often serves as a test sample to explore the performance of crystal technology.…”
Section: Introductionmentioning
confidence: 99%
“…Ambient, solution state techniques to create well‐defined metallic nanostructures over large areas are still limited. In an earlier report from our group, long (80 µm) nanowire (NW) arrays were made through electrospray ionization‐induced creation and deposition of Ag nanoparticles (NPs), under ambient conditions . These wires could be grown over several cm 2 areas to make a metallic grassland like morphology.…”
mentioning
confidence: 99%
“…A combination of all these effects led to high water capture efficiency (56.6 L d −1 m −2 ) at a prototype‐scale. Although we have used Ag NWs reported previously as the initial building block of our patterned NWs, the present work focuses on a method of creating hydrophilic‐hydrophobic patterned NWs using two simple steps, which mimic the above mentioned examples from nature and combine their special features to achieve highest water capture efficiency reported till date.…”
mentioning
confidence: 99%
See 1 more Smart Citation